We are Iraqis : aesthetics and politics in a time of war - Al-Ali, Nadje Sadig; Al-Najjar, Deborah (Contemporary issues in the Middle East., 2013)
While the occupation of Iraq and its aftermath has received media and political attention, we know very little about the everyday lives of Iraqis. Iraqi men, women, and children are not merely passive victims of violence, vulnerable recipients of repressive regimes, or bystanders of their country's destruction. In the face of danger and trauma, Iraqis continue to cope, preparing food, sending their children to school, socializing, telling jokes, and dreaming of a better future. Within the realm of imagination and creative expression, the editors find that many Iraqi artists have not only survived but have also sought healing. In We Are Iraqis, Al-Ali and Al-Najjar showcase written and visual contributions by Iraqi artists, writers, poets, filmmakers, photographers, and activists. Contributors explore the way Iraqis retain, subvert, and produce art and activism as ways of coping with despair and resisting chaos and destruction. The first anthology of its kind, We Are Iraqis brings into focus the multitude of ethnicities, religions, and experiences that are all part of Iraq.